Comparative analysis of different methods of retraction of the left lobe of the liver during laparoscopic sleeve gastrectomy - Kalashnikov, O. O.; Usenko, O. Yu.; Todurov, I. M.; Kosiukhno, S. V. (Modern medical technology, 2023)
The global obesity epidemic has led to the increasing popularity of bariatric surgeries. Laparoscopic sleeve gastrectomy is currently the most popular bariatric procedure for obesity. Retracting of the left liver lobe during laparoscopic sleeve gastrectomy is important for achieving an optimal surgical field. Aim. The aim of our study was to evaluate the results of using different methods of retraction of the left liver lobe during laparoscopic sleeve gastrectomy in patients with morbid obesity. Materials and methods. The 86 patients who underwent laparoscopic sleeve gastrectomy were divided into three groups based on the liver retraction method used: group 1 (ENDO RETRACT™ II), group 2 (Nathanson) and group 3 (Clickline Surgical Sponge Holder). All groups were evaluated in terms of demographic characteristics; liver function tests just before surgery and on the 1st and 2nd postoperative day (POD); developing complications and length of hospital stay. Results. The groups did not differ significantly in terms of demographic characteristics (p > 0.05). The Nathanson liver retractor (group 2) caused a significant rise in ALT and AST at POD 1 and POD 2 compared with group 1 and 3 (p < 0.05). The ENDO RETRACT™ II liver retractor (group 1) caused a higher incidence of liver injury than other groups. It led to statistical significance prolonged total operation time (p = 0.003), increased blood loss (p = 0.002) and prolonged postoperative hospital stay (p = 0.001) compared with other groups. Conclusions. The technique of left lobe retraction during laparoscopic sleeve gastrectomy using Clickline Sur- gical Sponge Holder is safe and effective. The use of this technique causes significantly less measurable liver damage and does not lead to an increase in the level of liver enzymes.